Respon Pertumbuhan Bibit Pinang Betara (Areca catechu L.) Pada Berbagai Konsentrasi Pupuk Organik Cair (POC) Supermes Dengan Media Tanam Tanah Ultisol di Polybag - Sandora, Amelia; Hayata, Hayata; Marpaung, Ridawati (Universitas Batanghari, 2025)
That's the important thing in areca nut nurseries is fertilization. The long term use of inorganic fertilizers can have a negative impact, the best solution to reduce the use of inorganic fertilizers is to use organic fertilizers . This study aims to determine the growth response of areca nut seedlings (Areca catechu L.) with the application of liquid organic fertilizer supermes on ultisol soil in polybags. This research was conducted from May 2024 to August 2024 at the BBI horticulture location. The design used in this study was a completely randomized design (CRD) with one factor, namely POC supermes, namely: s0 (control), s1 (2ml / l water), s2 (4ml / l water), s3 (6ml / l water), s4 (8ml / l water). Each treatment was repeated 3 times, so that there were 15 experimental units, each experimental unit consisted of 4 polybags, 3 polybags as sample plants. The parameters observed included plant height (cm), stem diameter (cm), dry weight of the crown (g), dry weight of the root (g), ratio of the root crown and seedling quality index. The results showed that the concentration of liquid organic fertilizer (POC) supermes 8 ml / l of water (s4) gave the best results, an increase in plant height of 10.20%, stem diameter 9.73%, dry weight of the crown 23.33%, dry weight of the root 57.76, ratio of the root crown 42.85% and seedling quality index 25.37% compared to the control.